Vitamin D status during normal pregnancy and postpartum. A longitudinal study in 141 Danish women - Milman, Nils; Hvas, Anne-Mette; Bergholt, Thomas (Journal of perinatal medicine, 2012)
Background/objectives: To assess vitamin D status during normal pregnancy and in the postpartum lactation period. Subjects/methods: The study comprised 141 healthy, ethnic Danish women with normal pregnancies, who were residents in Greater Copenhagen. Serum 25-hydroxy-vitamin D2+D3(25-OH-vitamin D) was measured at 18, 32 and 39 weeks’ gestation and 8 weeks postpartum. Results: There was a significant increase in 25-OH-vitamin D from 18 to 32 weeks’ gestation (P=0.0001) followed by a significant decrease from 32 to 39 weeks (P=0.001) as well as from 39 weeks to 8 weeks postpartum (P<0.0001). At 18, 32, 39 weeks’ gestation and 8 weeks postpartum, median 25-OH-vitamin D values were 77, 98, 91, and 73 nmol/L, respectively. During pregnancy and postpartum, none of the women displayed severe vitamin D deficiency (values <13 nmol/L). Between 1.4% and 4.3% of the participants displayed moderate vitamin D deficiency (values 13–24 nmol/L), 16–19% displayed vitamin D insufficiency (values 25–50 nmol/L), 77–84% had values >50 nmol/L and 0.7–2.8% had values >200 nmol/L. Conclusions: Low vitamin D status is frequent among pregnant Danish women, especially in late pregnancy and during lactation. Median dietary intake of vitamin D in women of reproductive age was 2.4 μg/day (10–90 percentile range=1.4–5.0). The recommendations for vitamin D supplementation prior to conception, during pregnancy and lactation should be reconsidered.